Erratum to: Type-4 spinors: transmuting from Elko to single-helicity spinors (The European Physical Journal C, (2019), 79, 4, (308) - Villalobos, C. H. Coronado; Rogerio, R. J. Bueno [UNESP]; Sabbas, E. F. M. T. São (Springer Nature, 2019)
The last co-Author’s name in the original manuscript is not correct.